FREQUENCY OF PULMONARY TOXICITY IN PATIENTS TREATED FOR HODGKIN LYMPHOMA (The Research of Medical Science Review, 2025)
Background: Pulmonary toxicity is an important concern in the treatment of Hodgkin lymphoma (HL), exceptionally among patients getting chemotherapeutic agents such as bleomycin. This research aimed to assess the frequency and severity of pulmonary toxicity in patients treated for Hodgkin lymphoma and to explore factors impact and its occurrence. Methods The study looked at 133 patients in which 94 males and 29 females diagnosed with Hodgkin lymphoma and received anti-cancer treatment including ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine). During treatment periods Lung function was monitored during and after treatment measures of oxygen saturation (SpO2), Diffusing Capacity of the Lung for Carbon Monoxide (DLCO), and Forced Vital Capacity (FVC). Pulmonary toxicity was categorized based on the degree of decline in these measures. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) version 22. Result: This study included 133 patients. The majority of patients (93%) kept their oxygen level well maintain spo2 during treatment while 4.5% experienced mild and 2.4% moderate drops in SpO2, suggesting mild to moderate lung toxicity. About DLCO result shows (90%) of the patients did not experience any decline in their DLCO values during treatment, indicating that their lung function remained stable while 13.5% of patients experienced a moderate decrease in their DLCO values and small portion of patients 1.5% severe decrease in DLCO. This study result shows 88.7% of patients, FVC (Forced Vital Capacity) remained stable while 3% of patients had severe drops in their lung capacity. Patients who received treatments containing bleomycin experienced a higher rate of lung problems. Conclusion: The frequency of pulmonary toxicity in patients treated for Hodgkin lymphoma was relatively low but remarkable specially among those encounter bleomycin-containing regimens. Although the majority of patients maintained stable lung function a small number of patients experienced varying degrees of lung toxicity. These findings underscore the importance of monitoring lung function in HL patients and suggest that future research should focus on reducing pulmonary side effects to improve long-term health outcomes.